Electrical Imaging: 2D Resistivity Tomography as a tool for Groundwater Studies at Mahmudia Village, West Sulaimani City, Iraqi Kurdistan Region - Aziz, Bakhtiar Kader (Sulaimani Journal for Pure and Applied Sciences, 2005)
Electrical Imaging (EI) is a geophysical method, developed over the past several years that provide a two or three dimensional resistivity model of the subsurface. EI can be very effective in providing information on the distribution of aquifers, aquitard, impermeable rocks, soil-bedrock interface topography, fracture zone, fault and voids. This technique is used for the first time in Iraq in Mahmudia village, west of Sulaimani City. Five traverses were taken; more than 4000 readings r.l'ere recorded using Wenner configuration with roll along technique. The data inversion u,as carried out by RES2DINV program using both finite difference and finite element mathematical methods. Two aquifers of different geological properties have been detected; one of them within the recent sediments while the other within the limestone beds of Sinjar Formation, These aquifers can be regarded as an excellent water resource fol providing sufficient groundwater to the area for domestic and agricultural purposes.